Baseline information and regionalization of the large river basins of Kazakhstan - Yapiyev, Vadim; Ongdas, Nurlan; Saidaliyeva, Zarina; Zhiyenbek, Abdikaiym; Smogulova, Tomiris; Baigaliyeva, Marzhan; Prikaziuk, Egor (Frontiers in Water, 2025)
This paper presents a comprehensive baseline assessment and regionalization of Kazakhstan’s river basins, categorizing them into Northern and Southern hydrological regions based on distinct hydroclimatological characteristics, bioclimatic zones, and dominant river regimes. Overall, climate in the region can be characterized as cold and dry, with high seasonality and spatial variability in air temperature and precipitation. The Northern region, characterized by nival regimes and rain-fed agriculture, contrasts sharply with the Southern region, dominated by nival-glacial regimes and irrigation-dependent agriculture. This regionalization reveals crucial differences in flood risk, water management strategies, and climate change adaptation needs. We also provide baseline regional river basin characteristics (drainage areas, elevation, mean annual temperature) and water balance components (annual precipitation, potential and actual evaporation, land surface runoff). This paper highlights the significant knowledge gaps concerning groundwater resources, water quality in Northern basins, and the impacts of climate change on freshwater ecosystems. The implications of this regionalization for water research and management in Kazakhstan and wider Central Asia are discussed in the context of addressing ongoing challenges like water scarcity, ecological conservation, and climate change adaptation. Building upon this regional framework, the study also outlines key knowledge gaps in areas such as water availability, quality, groundwater resources, and the applicability of hydrological models, suggesting important directions for future research in the region. The findings are intended to be a valuable resource for national and regional authorities, researchers, and policymakers. We advocate for a more systematic, transboundary approach to water resource characterization, considering hydrological and biophysical boundaries rather than solely national borders, which is crucial for addressing the complex water challenges facing Kazakhstan and Central Asia.